(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The author of this text reflects on the creative process of the show “Erradicação”, directed by Naomi Silman (Lume Teatro) in 2024. This analysis also allows for a reflection on the issue of memory, autofiction and alternative methods of scientific writing, which allow for a relationship between the creator and the researcher in a single process of art/research. The work oscillates between the biographical elements of the wandering author, autofiction inspired by the steps of his eradicated path between cultures and different social states. This text is made up of traveling memories, accounts of defragmentation and strategies for rewriting oneself through the artistic process.